Effect of grassland harvesting frequency and N-fertilization on stocks and dynamics of soil organic matter in the temperate climate. Issue 14 (6th December 2018) - Nüsse, Anja; Linsler, Deborah; Loges, Ralf; Reinsch, Thorsten; Taube, Friedhelm; Ludwig, Bernard
ABSTRACT: Management of grassland may affect the dynamics of soil organic carbon (SOC). Objectives were to analyze the effect of different harvesting frequencies and nitrogen fertilization regimes on SOC and total N stocks in a field trial on a sandy loam to loamy sand soil of a grassland site near Kiel (Germany). Additionally, effects on microbial biomass C (Cmic ) and ergosterol (as proxy for fungi) contents, water-stable aggregate size-classes and density fractions were studied. In the surface soil (0–10 cm), SOC and total N stocks, amounts of large water-stable macroaggregates (> 2000 µm) and contents of Cmic and ergosterol were significantly higher under a five cut regime. Cmic (rSpearman = 0.61) and ergosterol contents (rSpearman = 0.67) were correlated with amounts of large water-stable macroaggregates suggesting that fungi and microbial biomass play an important role in binding of small macroaggregates into large macroaggregates. The free light fraction of SOM showed significantly higher C concentrations under three cut compared to five cut at 30–60 cm, presumably related to the C/N ratio and the decomposability of root litter. This study indicates the importance of cutting frequency on SOC and total N stocks, amounts of large macroaggregates and contents of Cmic and ergosterol.